PP Relative clauses and intervention effects: comparing unergative and weather verbs - Marina R. A. Augusto; Elaine Grolla; Erica dos Santos Rodrigues (Fórum Linguístico)
The asymmetry between subject and object relative clauses has been attested in processing studies with adults (WANNER; MARATSOS, 1978; WARREN; GIBSON, 2002) and children (UTZERI, 2007; ADANI; SEHM; ZUKOWSKI, 2012). From the perspective of language acquisition, Friedmann, Belletti and Rizzi (2009) have suggested a formal treatment for this asymmetry in terms of intervention, and Costa et al. (2015) have expanded the proposal to PP relatives, considering data from European Portuguese. This study broadens that discussion by means of an elicitation experiment with  4 and 5-year-old children, speakers of Brazilian Portuguese. We contrast PP relatives with unergative verbs, showing intervention, and weather verbs, without intervention. Statistically significant differences between the types of verbs were obtained for younger children. We suggest that processing costs related to the availability of alternative less complex structures in the language is a major factor to be considered. This factor may impact the explanatory power of the intervention hypothesis.